Anodizing-assisted polishing method

Through the abrasive-free ECMP method, combined with the polishing technology of hard and soft abrasive particles and ultrasonic vibration, the problems of low efficiency and high cost of SiC polishing in the prior art are solved, and high-efficiency and low-cost high-precision polishing effect are achieved.

JP7628677B2Active Publication Date: 2025-02-12OSAKA UNIVERSITY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020132331
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-05
Filing Date
2020-08-04
Publication Date
2025-02-12
Estimated Expiration
2040-08-04

AI Technical Summary

Technical Problem

The chemical mechanical polishing (CMP) and electrochemical mechanical polishing (ECMP) methods in the prior art are inefficient when polishing single crystal SiC, and cannot effectively control pressure distribution and shape accuracy. The use of abrasives and electrolytes is costly, making it difficult to achieve efficient and low-cost high-precision polishing.

Method used

The electrochemical mechanical polishing method (ECMP) without abrasives is used to control the oxidation and polishing rates by applying fixed abrasive polishing body and anodizing process in the electrolyte, and the oxidation and polishing rates are controlled, and hard and soft abrasive particles are used for high-speed and low-speed polishing, combined with ultrasonic vibration to improve polishing efficiency and accuracy.

Benefits of technology

An efficient and low-cost polishing process is achieved, which significantly improves the polishing rate and shape accuracy of single crystal SiC, reduces surface damage, reduces production costs, and simplifies the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628677000001
    Figure 0007628677000001
  • Figure 0007628677000002
    Figure 0007628677000002
  • Figure 0007628677000003
    Figure 0007628677000003
Patent Text Reader

Abstract

To provide a polishing method with anodizing which greatly improves a material removal rate, has deep damage removal and high shape correction ability, and can be flattened with high accuracy without damage by a finish polishing process.SOLUTION: In slurryless ECMP, a high-speed polishing step of removing scratches and deep damage under the surface introduced during manufacturing at a high material removal rate of a workpiece, and a low-speed polishing step of removing an oxide caused by shallow damage, and flattening at a low material removal rate of a workpiece are performed in order, and damage introducing means that uniformly introduces shallow damage under the surface of the workpiece in the high-speed polishing step.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing method assisted by anodization, and more particularly to a polishing method assisted by anodization that is capable of creating a desired shape of anodizable, difficult-to-process material with high efficiency and high precision by combining oxidation and polishing. [Background technology]

[0002] The CMP (Chemical Mechanical Polishing) process has been developed as a method for polishing the surface of single crystal SiC for power device fabrication without causing damage, but the polishing rate is very slow at about 1μm / h, and the costs of purchasing the polishing liquid called slurry and disposing of the waste liquid are high, which increases the production costs of wafers, and there is a demand for the development of a highly efficient and low-cost polishing method. CMP is unable to control the pressure distribution in the contact area due to the application of a soft polishing pad and the uneven distribution of the polishing body. Therefore, this polishing method cannot correct the shape accuracy.

[0003] In addition, Non-Patent Document 1 discloses ECMP (Electro-Chemical Mechanical Polishing) for electrochemically and mechanically polishing SiC. In this ECMP, an electrode is placed on the back of a polishing pad, and SiC is used as an anode, and polishing is performed while passing a current of a predetermined current density, using a solution in which silica slurry is dispersed in KNO3 or H2O2. Here, if the surface oxidation and polishing of SiC are carried out simultaneously, a processing speed of 0.4-0.5 μm / h can be obtained, but scratches cannot be removed. This is because the oxidation rate by anodization is higher than the polishing rate, so if oxidation and polishing are carried out simultaneously, processing does not proceed. Therefore, the oxidation step and the polishing step are separated, and the oxidation step is carried out for 30 seconds and the polishing step for 30 minutes, and by repeating this, it is possible to remove surface waviness and roughness. It has also been reported that increasing the current density increases the processing speed, but the surface roughness deteriorates.

[0004] Therefore, the inventor Yamamura proposed a polishing method that uses a polishing pad and anodization (Patent Document 1). Patent Document 1 discloses a polishing method that includes an anodization process in which a workpiece is used as an anode in the presence of an electrolyte, a voltage is applied to pass a current of a predetermined current density to form an oxide film on the surface of the workpiece, and a polishing process in which the oxide film is selectively polished and removed with a polishing pad made of an abrasive material having an intermediate Mohs hardness between the workpiece and the oxide film and having a built-in electrode that serves as a cathode, and in which the workpiece and the polishing pad are placed in an electrolyte, the anodization process in which a voltage is applied to the workpiece and the electrode of the polishing pad to form an oxide film, and the polishing process in which the oxide film of the workpiece is polished and removed with the polishing pad in the electrolyte are simultaneously carried out, and the surface of the workpiece is planarized under conditions in which the polishing rate by the polishing process is higher than the oxidation rate by the anodization process.

[0005] In the polishing method described in Patent Document 1, the surface of SiC is first modified by anodization, and then the modified layer is removed by a soft polishing material (abrasive grains). Since the hardness of the soft polishing material is lower than that of SiC, scratches and subsurface damage are not induced on the SiC surface, and only the modified layer can be removed. This polishing method is said to be applicable to CVD-SiC, sintered SiC, single crystal GaN, or cemented carbide in addition to single crystal SiC. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6329655 [Non-patent literature]

[0007] [Non-Patent Document 1] Li.C,et.al.,J.Electron.Mater.33(2004)481-486 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the polishing method described in Patent Document 1 uses an electrolyte mixed with a slurry, and the anodization process and the polishing process are carried out simultaneously in the electrolyte. However, soft abrasive materials are used in all polishing steps, and soft polishing pads are used as in CMP, so the polishing rate in the polishing process is slow, and therefore the overall removal rate is slow and the ability to correct shape accuracy is low.

[0009] On the other hand, when a fixed abrasive polishing pad is applied to ECMP, the abrasive parameters can be determined depending on the type of polishing pad, so that the anodizing parameters and the abrasive parameters can be controlled separately, which is expected to significantly improve ECMP performance, i.e., to achieve higher efficiency and precision.

[0010] In view of the above-mentioned situation, the present invention aims to provide a polishing method that does not use a slurry, but instead employs a fixed abrasive polishing body and anodizing, which introduces a high-speed polishing process with increased anodizing rate and polishing rate, thereby significantly improving the material removal rate, providing the ability to remove deep damage and correct shape with high precision, and enabling a damage-free, high-precision planarization by a finish polishing process. [Means for solving the problem]

[0011] In order to solve the above-mentioned problems, the present invention provides a polishing method and an apparatus using anodization, which are configured as follows.

[0012] (1) In the presence of an electrolyte, an anodizing process in which a voltage is applied to a workpiece as an anode to oxidize the surface of the workpiece; a polishing process in which oxides formed on the surface of the workpiece are polished and removed using a fixed abrasive polishing body having abrasive grains of a predetermined hardness and grain size fixed to a substrate; and (c) simultaneously or alternately proceeding with a polishing rate in the polishing process higher than an oxidation rate in the anodizing process, a high-speed polishing process that provides a high material removal rate for the workpiece, even removing scratches and deep subsurface damage introduced during manufacture; a low-speed polishing step in which the material removal rate of the workpiece is low and oxides resulting from shallow damage are removed and planarized; and the high-speed polishing step is provided with a damage introducing means for introducing uniformly shallow damage under the surface of the workpiece.

[0013] (2) The polishing method with the aid of anodization according to (1), wherein the high-speed polishing step uses a hard fixed abrasive polishing body having hard abrasive grains fixed to a substrate, the hard abrasive grains being harder than the workpiece.

[0014] (3) The polishing method using anodic oxidation according to (2), wherein the high-speed polishing step is performed under high current density conditions in which the potential of the workpiece is set to a high potential higher than the passive potential of the oxide.

[0015] (4) The polishing method using anodization according to (1), wherein the low-speed polishing step uses a soft fixed abrasive polishing body having soft abrasive grains fixed to a substrate, the soft abrasive grains having a hardness lower than that of the workpiece and higher than that of oxides.

[0016] (5) The polishing method using anodic oxidation according to (4), wherein the low-speed polishing step includes a finish polishing step in which the potential of the workpiece is set to a low potential equal to or lower than the passive potential of the oxide under a low current density condition.

[0017] (6) The polishing method using anodic oxidation according to (5), wherein the low-speed polishing step includes a rough polishing step, which is performed before the finish polishing step, under a high current density condition in which the potential of the workpiece is set to a high potential higher than the passive potential of an oxide.

[0018] (7) The polishing method using anodization described in any one of (1) to (6), wherein the damage introduction means is friction between a hard fixed abrasive polishing body having hard abrasive grains harder than the workpiece fixed to a substrate and the surface of the workpiece.

[0019] (8) The polishing method using anodization according to any one of (1) to (7), wherein ultrasonic vibration is applied to the polishing surface from the workpiece side or from the fixed abrasive polishing body side.

[0020] (9) The polishing method with the aid of anodization according to (8), wherein the damage introduction means is ultrasonic vibration applied to the polishing surface.

[0021] (10) The polishing method utilizing anodization according to any one of (1) to (9), wherein the temperature of the electrolytic solution is controlled.

[0022] (11) The method for polishing with the aid of anodization according to any one of (1) to (10), wherein the workpiece is single crystal SiC.

[0023] (12) The method for polishing with the aid of anodization according to (2) or (7), wherein the hard fixed abrasive polishing body is a diamond grindstone having an average grain size of 1 μm (range of 0.5 to 2 μm, #8000).

[0024] (13) The method for polishing with the aid of anodization according to (4), wherein the soft fixed abrasive polishing body is a ceria grinding wheel. Effect of the Invention

[0025] By optimizing the polishing conditions and anodizing conditions in the conventional polishing method utilizing anodization, the present invention can realize a high-speed polishing process that can replace the grinding and lapping processes used in the process of slicing an ingot to produce wafers. Also, although it is a low-speed polishing process, it is possible to flatten the surface with high precision while removing subsurface damage through the rough polishing and finish polishing processes, and since no slurry, which requires processing costs, is used in any of the processes, it is possible to simultaneously achieve high efficiency and low costs.

[0026] ECMP using hard abrasive grains has achieved a polishing speed of 63μm / h in SiC polishing, which is more than 60 times faster than conventional CMP (1μm / h), and can significantly reduce the processing time required to manufacture SiC wafers. In addition, by combining rough polishing using high-potential, high-current density conditions and finish polishing using low-potential conditions below the passive potential, it is possible to manufacture high-quality wafers of device grade while maintaining high polishing efficiency.

[0027] In ECMP, the oxidation rate saturates even if the current density is increased, so the polishing rate cannot be increased, but by increasing the temperature of the electrolyte, the oxidation rate saturation value increases, and the polishing rate can be significantly increased. In addition, in the case of constant potential mode, the oxidation rate and polishing rate of SiC increase exponentially by increasing the electrolyte temperature. Therefore, the polishing rate of ECMP can be significantly improved by increasing the temperature of the electrolyte at all polishing stages of ECMP.

[0028] In polishing SiC, it was found that the polishing rate when ultrasonic vibration was applied was about four times that when ultrasonic vibration was not applied at the same electrolyte temperature. The effect of increasing the material removal rate (MRR) by applying ultrasonic vibration is clear. [Brief description of the drawings]

[0029] [Figure 1] FIG. 2 is an explanatory diagram showing a polishing step of the present invention. [Diagram 2] FIG. 1 is a simplified explanatory diagram showing a flattening polishing apparatus according to a first embodiment of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram of a polishing mechanism. [Figure 4] FIG. 4 is a simplified explanatory diagram showing a local polishing apparatus according to a second embodiment of the present invention. [Diagram 5] 1 is a graph of LSV results showing the relationship between the anodization of 4H—SiC and the potential. [Figure 6] These are AFM images showing the surface state at each anodization potential. [Figure 7] The figures show AFM images and cross-sectional shapes of the anodized state around an indent formed by a nanoindenter. (a) shows the formed indent, (b) shows the state after anodization at 10 μA for 30 s, and (c) shows the state after anodization at 10 μA for 60 s. [Figure 8](a) and (b) show an SEM image and energy dispersive X-ray (EDX) measurement results of the oxidized surface obtained by oxidizing the CMP-treated surface at 7 V for 1 minute, and (c) and (d) show an SEM image and EDX measurement results of the oxidized surface obtained by oxidizing the CMP-treated surface at 7 V for 10 minutes, removing the oxide film with hydrofluoric acid, and then oxidizing it again at 7 V for 1 minute. [Figure 9] The results of measurements taken by Raman spectroscopy are shown, where (a) shows the sliced ​​surface of SiC (Slicing), (b) shows the diamond polished surface (Lapping), and (c) shows the ECMP treated surface (ECMP). [Figure 10] Scanning white light interferometry (SWLI) images of SiC surfaces mechanically polished with different abrasives (ceria, alumina, and diamond). [Figure 11] 1 is a graph showing cross-sectional views of polished surfaces polished with different polishing bodies (ceria, alumina, diamond) using MP. [Figure 12] SWLI images of SiC surfaces treated by ECMP using different abrasives (grinding wheels): (a) ceria abrasive, (b) alumina abrasive, (c) #20000 diamond wheel, and (d) #8000 diamond wheel. [Figure 13] 13 is a graph showing the machining depth of a SiC surface treated by ECMP using different abrasive bodies (grinding wheels). [Figure 14] The polishing results of MP and ECMP using a #8000 ceria grinding wheel are shown. The left side shows the polished surface of MP, the center shows the polished surface of ECMP, and the right side shows the polishing depth. [Figure 15] The polishing results of MP and ECMP using a #8000 alumina grinding wheel are shown. The left side shows the polished surface of MP, the center shows the polished surface of ECMP, and the right side shows the polishing depth. [Figure 16] The polishing results of MP and ECMP using a #20000 diamond grinding wheel are shown. The left side shows the polished surface of MP, the center shows the polished surface of ECMP, and the right side shows the polishing depth. [Figure 17]The polishing results of MP and ECMP using a #8000 diamond grinding wheel are shown. The left side shows the polished surface of MP, the center shows the polished surface of ECMP, and the right side shows the polishing depth. [Figure 18] The left side shows a SWLI image of the sliced ​​SiC surface, the center shows a SWLI image of the SiC surface after 20 minutes of ECMP using a #8000 diamond wheel, and the right side shows a SWLI image of the SiC surface after an additional 30 minutes of ECMP with a ceria wheel. [Figure 19] 1 is a graph showing the polishing depth of a SiC surface after ECMP with a #8000 diamond wheel and after additional ECMP with a ceria wheel. [Figure 20] The image on the left shows a SWLI image of the as-sliced ​​SiC surface, the center image shows a SWLI image of the SiC surface obtained by rough ECMP, and the right image shows a SWLI image of the SiC surface after polishing by finish ECMP. [Figure 21] (a) shows an AFM image of the surface obtained by rough ECMP, and (b) shows an AFM image of the surface obtained by finish ECMP. [Figure 22] FIG. 13 is a simplified diagram showing a polishing apparatus according to a third embodiment, which is an ultrasonically assisted electrochemical mechanical polishing (UAECMP) apparatus in which ultrasonic vibration is added to a slurry-less ECMP. [Figure 23] FIG. 1 is a conceptual diagram showing a cross section of the state in which ultrasonic vibration is applied while the tips of the abrasive grains of the grinding wheel are pressed against the polishing surface of the SiC wafer. [Figure 24] 1 is a graph showing the results of examining the depth of anodization when ultrasonic vibration is applied and when it is not applied. [Diagram 25] (a) A graph comparing the oxidation depth with and without ultrasound, (b) an image showing the surface condition without ultrasound, and (c) an image showing the surface condition with ultrasound. [Figure 26] 1 is a graph showing the polishing depth in ECMP using a ceria grinding wheel with and without ultrasonic waves. [Figure 27] 1 is a graph comparing oxidation depths with and without ultrasonic waves using quartz glass to evaluate oxide film removal characteristics. [Figure 28] The results of UAECMP with an increased removal rate are shown. (a) is an image of the surface condition, and (b) is the result of XPS measurement. [Figure 29] The image on the left is an AFM image of the surface of a SiC wafer polished by UAECMP, the center is an image showing the residual stress in the depth direction of the diamond-lapped surface observed with a confocal Raman microscope, and the image on the right is an image showing the residual stress in the depth direction of the surface polished by UAECMP observed with a confocal Raman microscope. [Diagram 30] 1 shows a polishing apparatus according to a fourth embodiment, where (a) is a conceptual diagram of a high-speed polishing apparatus using a hard fixed-abrasive polishing body, and (b) is a conceptual diagram of a low-speed polishing apparatus using a soft fixed-abrasive polishing body. [Diagram 31] FIG. 13 is a conceptual diagram showing a polishing apparatus according to a fifth embodiment, which is a composite polishing apparatus that combines a hard fixed-abrasive polishing body and a soft fixed-abrasive polishing body and realizes each polishing mode by raising and lowering the body. [Diagram 32] 1 is a graph showing the relationship between polishing time and electrolyte temperature for ECMP and UAECMP. [Diagram 33] 1 is a graph showing the relationship between the temperature of the electrolytic solution and the oxidation depth in constant potential oxidation. [Diagram 34] 1 is a graph showing the relationship between current density and oxidation depth when the temperature of the electrolyte is 25, 40, and 60° C. [Diagram 35] The images show residual stress in the depth direction observed with a confocal Raman microscope when a SiC wafer was mechanically polished with a ceria grinding wheel. The left side shows the result of 30 minutes of mechanical polishing, the center shows the result of 30 minutes of mechanical polishing with ultrasonic vibration applied, and the right side shows the result of mechanical polishing with 1 minute of ultrasonic vibration applied. [Diagram 36] 1 is a graph showing the relationship between electrolyte temperature and material removal rate (MRR) for ECMP and UAECMP at constant potential. [Figure 37] FIG. 13 is a simplified explanatory diagram showing a local polishing apparatus having a temperature control function according to a sixth embodiment. [Figure 38] FIG. 13 is a simplified explanatory view showing a flattening polishing apparatus to which ultrasonic vibration is applied according to a seventh embodiment. [Figure 39]FIG. 13A is a simplified cross-sectional view of a flattening polishing apparatus according to a seventh embodiment, and FIG. [Diagram 40] FIG. 13 is a simplified explanatory diagram showing a modified example of the flattening polishing apparatus of the seventh embodiment. [Diagram 41] 13A and 13B show a local UAECMP apparatus according to an eighth embodiment, in which (a) is a perspective view of the main parts, and (b) is a partial cross-sectional view of the polishing head. [Diagram 42] 13A and 13B show a local UAECMP apparatus according to a ninth embodiment, in which (a) is a perspective view of a main part, and (b) is a simplified cross-sectional view showing the overall configuration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The present invention is based on a polishing method using anodization, which simultaneously or alternately performs an anodization process in which a voltage is applied to the workpiece as an anode in the presence of an electrolyte to oxidize the surface of the workpiece, and a polishing process in which an oxide formed on the surface of the workpiece is polished and removed with a fixed abrasive polisher having abrasive grains of a specified hardness and grain size fixed to a substrate, under conditions in which the polishing rate of the polishing process is higher than the oxidation rate of the anodization process. Here, it is important that a slurry is not used in normal CMP, but a slurry is not used in ECMP (Electro-Chemical Mechanical Polishing) according to the present invention.

[0031] The present invention is characterized in that a high-speed polishing process, in which the material removal rate (MRR) of the workpiece is high and scratches and deep subsurface damage introduced during manufacture are removed, and a low-speed polishing process, in which the material removal rate of the workpiece is low and oxides resulting from shallow damage are removed and flattened, are carried out in that order, and the high-speed polishing process is provided with a damage introduction means for introducing uniform shallow damage into the subsurface of the workpiece.

[0032] Here, the high-speed polishing step uses a hard fixed abrasive polishing body in which hard abrasive grains having a harder hardness than the workpiece are fixed to a substrate, and the high-speed polishing step is preferably performed under high current density conditions in which the potential of the workpiece is set to a high potential higher than the passive potential of oxides in order to increase the material removal rate.

[0033] Here, the low-speed polishing step uses a soft fixed abrasive polishing body in which soft abrasive grains, which are harder than the workpiece and harder than the oxide, are fixed to a substrate, and the low-speed polishing step includes a finish polishing step in which the potential of the workpiece is set to a low potential equal to or lower than the passive potential of the oxide under a low current density condition, thereby flattening the surface with high accuracy.

[0034] Furthermore, the low-speed polishing step preferably includes a rough polishing step before the finish polishing step, in which the potential of the workpiece is set to a high potential higher than the passive potential of the oxide under a high current density condition. This rough polishing step can remove all shallow damage remaining under the surface of the workpiece.

[0035] The damage introduction means is based on friction between the surface of the workpiece and a hard fixed abrasive polishing body, which has hard abrasive grains that are harder than the workpiece and fixed to a substrate. In other words, the hard fixed abrasive polishing body used in the high-speed polishing process also serves as a means for introducing shallow damage below the surface of the workpiece.

[0036] Furthermore, in the present invention, it is more preferable to apply ultrasonic vibration to the polishing surface from the workpiece side or the fixed abrasive polishing body side. By applying ultrasonic vibration to the polishing surface, the chemical reaction of anodization is promoted by the bursting of cavitation generated near the surface of the workpiece, and it also contributes to efficiently generating shallow damage under the surface that comes into contact with the abrasive grains of the hard fixed abrasive polishing body, so that not only does it increase the anodization rate, but it also contributes to removing oxides, so that the polishing rate can be increased.

[0037] More specifically, no matter how carefully a material is processed, a certain amount of damage remains below the surface, such as cracks, residual stress, contamination, and voids, which is called subsurface damage (SSD). In this invention, damage that occurs below the surface of a workpiece is referred to as "SSD." SSD may occur during the manufacturing process or may be due to the type or quality of the material used. In this invention, "deep" means on the order of tens of μm, and "shallow" means on the order of a few μm.

[0038] In the present invention, "hard" or "hard" refers to a property of being harder than the workpiece, and "soft" or "soft" refers to a property of being harder than the workpiece. Incidentally, the Vickers hardness is as follows: SiC: 24-28 GPa, alumina (Al2O3): 12-23 GPa, silica (SiO2): 7.6 GPa, ceria (CeO2): 5-7.5 GPa. Diamond is harder than SiC.

[0039] In 4H-SiC(0001), a passive film is stably formed when the anodization potential is in the range of 1.9 to 3.5 V, and the passive film begins to break down when the potential exceeds 3.5 V, so in the present invention, 3.5 V is defined as the passive potential, and anything above the passive potential is defined as a high potential, and anything below the passive potential is defined as a low potential. Note that if the potential of the workpiece is lower than 1.9 V, anodization does not occur, so 1.9 V is the lower limit of the low potential.

[0040] The present invention can be applied to the workpiece as long as it is a material that is conductive and can be anodized, and examples of such materials include single crystal SiC, CVD-SiC, sintered SiC, single crystal GaN, Si3N4, AlN, and cemented carbide such as WC. In the following embodiment, the polishing of a 4H-SiC (0001) wafer for fabricating a power device will be described as an example of the workpiece.

[0041] If damage (residual strain or microcracks from the previous process) exists on the surface of the workpiece, the reaction activity is high, so the anodization rate is high, and as a result, the polishing rate of ECMP is also high. However, if the residual damage is removed, the anodization rate and the polishing rate that depends on it also decrease. In the present invention, as shown in Figure 1, a polishing body (grinding stone) containing abrasive grains harder than the workpiece is used to form shallow damage on the surface while anodization is performed, thereby maintaining a high polishing rate, and when the removal of deep damage is completed, a polishing body containing soft abrasive grains is applied to perform finish polishing. This allows the deep damaged layer of the workpiece to be removed with high efficiency.

[0042] In ECMP, increasing the current density increases the oxidation rate and therefore the polishing rate, but the surface roughness worsens due to the formation of protruding oxides. In the case of SiC, it has been found that by setting the applied voltage to 3.5V or less (e.g. 3V), which is the condition for forming a passivation film, the oxidation rate is greatly reduced, but the surface roughness is greatly improved due to the formation of a uniform oxide protective film. By performing high-speed polishing under high current density conditions for rough polishing and low voltage conditions for finish polishing, it is possible to achieve both highly efficient polishing and a low surface roughness finish.

[0043] As a result, ECMP using hard abrasive grains under high-speed polishing conditions achieved 63μm / h in SiC polishing, which is more than 60 times faster than conventional CMP (1μm / h), and can significantly shorten the processing time required for SiC wafer manufacturing. In ECMP using soft abrasive grains under low-speed polishing conditions, finishing polishing and rough and finish polishing can be performed, making it possible to manufacture high-quality device-grade wafers while ensuring high polishing efficiency.

[0044] Next, the polishing method of the present invention will be described with reference to Fig. 1. First, as shown in Fig. 1(a), undulations, saw marks, and deep SSDs are present on the surface of a SiC wafer after slicing an ingot.

[0045] 1(b) to (d) show the high-speed polishing process. The high-speed polishing process is a process in which the material removal rate of the workpiece is high, and waviness, scratches introduced during manufacturing, and deep damage under the surface are removed and flattened. A hard fixed abrasive polishing body having hard abrasive grains harder than the workpiece fixed to a substrate is used, and the potential of the workpiece is set to a high potential higher than the passive potential of the oxide, under high current density conditions. The high-speed polishing process is characterized by the present invention, and is provided with a damage introduction means for introducing shallow damage under the surface of the workpiece. In reality, shallow damage is uniformly introduced to the workpiece by friction between the hard fixed abrasive polishing body and the surface of the workpiece. Since anodic oxidation occurs preferentially from this damage, uniformity of the introduced shallow damage is important, but this is guaranteed if the distribution of hard abrasive grains in the hard fixed abrasive polishing body is uniform.

[0046] 1(e)-(h) show the low-speed polishing process. The low-speed polishing process is a process in which the material removal rate of the workpiece is low, and oxides caused by shallow damage are removed to flatten the surface roughness to the order of sub-nanometers. The low-speed polishing process uses a soft fixed abrasive polishing body in which soft abrasive grains having a hardness lower than the workpiece and higher than the oxide are fixed to a substrate, and the potential of the workpiece is set to a low potential below the passivation potential of the oxide under a small current density condition (see Figs. 1(g) and (h)). Furthermore, the low-speed polishing process includes a rough polishing process (see Figs. 1(e) and (f)) before the finish polishing process, in which the potential of the workpiece is set to a high potential higher than the passivation potential of the oxide under a large current density condition. The rough polishing process removes the shallow damaged layer on the SiC surface, and the finish polishing process finishes the surface roughness to the order of sub-nanometers. The rough polishing process may be omitted, and the high-speed polishing process may be followed by the finish polishing process.

[0047] On the sliced ​​SiC surface, there are many saw marks on the surface and deep SSDs below the surface. In ECMP, the entire SiC surface is oxidized, and the sites of SSDs are preferentially oxidized. In the initial polishing stage, only the convex oxide regions on the surface are removed, and the concave regions are still covered with an oxide layer (see Fig. 1(b)). Therefore, due to the barrier caused by the oxide layer, the oxidation rate of the convex regions must be greater than that of the concave regions, but the oxidation rate is larger in the convex regions because shallow SSDs are introduced in them due to friction with the hard abrasive grains. By repeating the anodization and removal of the oxide layer, the saw marks are gradually removed and the SiC surface gradually becomes flat (see Fig. 1(c)). After the saw marks are removed, there are still many deep SSDs and newly introduced shallow SSDs below the SiC surface, resulting in a high oxidation rate. Thus, the deep SSDs and residual oxides are removed, and all are only shallow SSDs (see Fig. 1(d)). At this stage, high-speed polishing is no longer necessary, and low-speed polishing is switched to. The rough polishing process removes almost all shallow SSD (see Fig. 1(e) and (f)), and then the finish polishing process further improves the surface roughness (see Fig. 1(g) and (h)).

[0048] All of these processes use fixed abrasive polishing bodies (grindstones) with abrasive grains fixed to a substrate, and do not use slurry, which is expensive and requires high waste disposal costs, so costs can be reduced. Fixed abrasive polishing bodies are also suitable for removing waviness from workpieces, and are also advantageous for flattening in the low spatial wavelength region. EXAMPLES

[0049] FIG. 2 shows a planarization polishing apparatus according to a first embodiment of the present invention, which uniformly polishes a SiC wafer and produces a high-quality wafer of device grade. As shown in FIG. 2, a SiC wafer 1 as a workpiece is fixed on a wafer holder 4 with an insulating layer 3 attached to the tip of a spindle 2 and contacts a grinding wheel 5. The grinding wheel 5 is attached to a metal plate 7 with a large number of fan-shaped openings 6. The metal plate 7 is placed on a rotating table 9 with an insulating layer 8. The SiC wafer 1, the grinding wheel 5, and the metal plate 7 are immersed in an electrolyte 10. In the slurry-less ECMP, the SiC wafer 1 is used as a working electrode (WE), and a positive potential is applied through the wafer holder 4, and the metal plate 7 is used as a counter electrode (CE), and a negative potential is applied. A reference electrode (RE) is used to precisely control the potential applied to the SiC wafer 1, and this process is controlled by a potentiostat 11. A partition is provided around the rotating table 9 to form a container 12 for holding the electrolyte 10, and the grindstone 5, metal plate 7, and SiC wafer 1 held by the wafer holder 4 are positioned in the container and immersed in the electrolyte 10. Thus, the potentiostat 11, wafer holder 4, SiC surface, electrolyte 10, and metal plate 7 form an electric circuit. The SiC surface can be anodized by the applied positive potential, and the oxidation rate can be controlled by controlling the potential using the potentiostat 11. The polishing rate can also be controlled by the type of grindstone 5 and the pressure with which the SiC wafer 1 is pressed against the grindstone 5.

[0050] The polishing mechanism of the present invention is shown in Figure 3. First, the surface of the SiC wafer 1 is modified by anodization, and a modified layer is generated on the SiC surface (Figure 3(a)). After that, the modified layer is removed by the grindstone 5 (Figure 3(b)). In the initial stage of ECMP, only the convex oxide regions on the surface are removed, while the concave regions are still covered with the oxide layer 13 (Figure 3(c)). Therefore, the oxidation rate of the convex regions must be greater than that of the concave regions due to the barrier caused by the oxide layer 13. SSD 14 is shown in Figure 3(a). It has been confirmed that anodization occurs preferentially from SSD 14. It has also been confirmed that when the abrasive grains of the grindstone 5 are harder than SiC, a shallow SSD is introduced under the surface as polishing proceeds. By replacing this grindstone 5, it can be used for high-speed polishing processes or low-speed polishing processes. By repeating the anodization and oxide removal, the surface gradually becomes flat, and a damage-free surface is obtained. Compared with conventional polishing techniques such as mechanical polishing and CMP, the slurry-less ECMP of the present invention is expected to have the following advantages:

[0051] First, highly efficient polishing is expected. The material removal rate (MRR) of slurry-less ECMP is mainly controlled by the anodization rate of the SiC surface. It has been found that the anodization rate of n-type SiC can reach 53 nm / min and that of p-type SiC can reach 1.3 μm / min. In slurry-less ECMP, the MRR is further improved by enhancing the ion exchange rate and the force due to the polishing motion and pressure. Moreover, the anodization rate is proportional to the current, and the MRR can be quantitatively controlled by the current, which also improves the performance of slurry-less ECMP.

[0052] Secondly, damage-free polishing can be expected. In the final polishing process of slurry-less ECMP, the SiC surface is first modified by anodization, and then the modified layer is removed by a soft fixed abrasive polishing body. Unlike conventional fixed abrasive polishing, the hardness of the abrasive is much lower than that of SiC, so only the modified layer is removed and no scratches or SSD are generated on the SiC surface. Therefore, the shortcomings of conventional hard fixed abrasive polishing are overcome, and its planarization ability is fully utilized.

[0053] Third, manufacturing costs can be reduced. In slurry-less ECMP, an electrolyte is used instead of a slurry. Unlike conventional modification techniques that apply strong oxidizing agents, neutral electrolytes such as sodium chloride (NaCl), potassium chloride (KCl), and sodium nitrate (NaNO3) can be applied to the anodization of SiC. Furthermore, the use of a fixed abrasive structure polishing body (grinding wheel or polishing pad) can significantly reduce electrolyte waste. Furthermore, there are no extra expensive parts in the slurry-less ECMP device, which can reduce costs.

[0054] Finally, the simplification of the manufacturing process of SiC wafers is expected. Not only for the final finishing of SiC wafers, slurry-less ECMP is also very promising for the application in processing sliced ​​or roughly ground / lapped SiC wafers due to its high MRR and planarization ability. If the manufacturing process of SiC wafers can be simplified, the manufacturing cost of SiC wafers can be further reduced and the production efficiency can be greatly improved. EXAMPLES

[0055] FIG. 4 shows a local polishing apparatus according to a second embodiment of the present invention. The SiC wafer 21 was fixed on a copper plate 23 placed on an XY table 22 in an insulating state and served as a working electrode (WE). The tip of the spindle 24 was used as a counter electrode (CE). A grinding wheel 25 was attached to the tip of the spindle 24 to contact the SiC surface. The SiC surface, the grinding wheel, and the tip of the spindle 24 were immersed in an electrolyte 27 in a container 26. A potentiostat 28 was applied to control the anodization parameters for anodizing the SiC surface, and a load was applied to the spindle 24, and the grinding wheel 25 was rotated at a specific speed while anodizing to remove the oxide layer. In this way, localized slurry-less ECMP is realized.

[0056] The tip area of ​​the spindle 24 is divided into four, and a 1 / 4-shaped grindstone 25 is fixed at the opposing position via an elastic body, and the other area becomes an electrode 29. That is, the grindstone 25 and the electrode 29 are arranged alternately in the rotation direction. The spindle 24 is connected to the counter electrode (CE) terminal of the potentiostat 28 via a slip ring 30. Furthermore, an electrolyte supply pipe 31 is arranged in the center of the spindle 24, and is connected to a circulation pump 33 via a rotary joint 32 at the upper end. The electrolyte collected from the container 26 is supplied to the tip of the supply pipe 31 by the circulation pump 33, so that fresh electrolyte is always supplied to the polishing surface. In addition, a pressurizing means for applying a polishing pressure is also provided at the upper end of the spindle 24. By driving the XY table 22, the SiC wafer 21 is displaced relative to the spindle 24 together with the container 26.

[0057] <Relationship between anodization of 4H-SiC and potential> Linear scan voltammetry (LSV) was performed to investigate the relationship between the oxide protrusions and the oxidation potential. The LSV conditions were electrolyte: 1 wt% NaCl aqueous solution, scan rate: 5 mV / s, and scan range: 0–9.8 V. The oxidation potential was precisely controlled by referring to an Ag|AgCl electrode. Figure 5 shows the LSV results for a 4H-SiC(0001) substrate. The inset shows an enlargement of the graph from 0 to 5 V. The results showed similar I-V curves to those for general metal anodization with five oxidation periods. a–b (0–1.9 V) are the non-oxidized state, b–c (1.9–2.4 V) are the active state, c–d (2.4–3.5 V) are the passive state, d–e (3.5–6 V) are the transient state, and e–f (6–9.8 V) are the transpassive state. This indicates that anodization occurs when the potential exceeds 1.9 V, the passive film suppresses oxidation between 1.9 and 3.5 V, and the passive film is destroyed and oxidation increases rapidly when the potential exceeds 3.5 V. In the present invention, the finish polishing step is performed at a potential that does not destroy the passive film, and the high-speed polishing step and the rough polishing step are performed at a potential that destroys the passive film.

[0058] An anodic oxidation experiment was conducted to verify the results of LSV. The SiC substrate was anodically oxidized for 2 minutes at potentials of 1 V (unoxidized state), 3 V (passive state), 5 V (transient state), 7 V, and 9 V (trans - passive state). The results of observing the oxidized surface by AFM are shown in Fig. 6. A step - terrace structure was observed on the commercially available SiC surface. It was found that the terraces became smoother at 3 V and 5 V, which is due to the passivation of the surface. Oxide protrusions were generated on the surface oxidized at 7 V. Combining these phenomena with the results of LSV, it was found that the oxide protrusions are generated by the breakdown of the passive film.

[0059] <Preferential Anodic Oxidation from SSD> First, using a nano - indenter (ENT - 2100, Elionix Inc), 400 indentations (20×20) separated by 5 μm were formed on the SiC substrate surface with a force of 100 mN. Fig. 7 shows the change of the indentations in the anodic oxidation process. Fig. 7(a) shows the untreated indentations. As shown in Fig. 7(b), it was found that the indentations were oxidized in the first 0.5 minutes of oxidation, and the oxidation started from the entire surface of the indentations. As shown in Fig. 7(c), the oxidation rate of the indentations was very high, and the height of the oxide protrusions located at the edges of the indentations reached more than 100 nm within 1 minute. On the other hand, the oxidation rate of the region without indentations was very slow, and it was found that the height of the oxide protrusions in this region reached only about 30 nm even after 1.5 minutes of oxidation. This indicates that the indentations were preferentially oxidized in the anodic oxidation process. Since these indentations were mechanically formed by the nano - indenter, a damage layer was undoubtedly introduced on and directly below the surface of the indentations. This phenomenon reveals that the damage layer has a lower breakdown potential and a higher oxidation rate than atomic pits.

[0060] Figures 8(a) and (b) show SEM images and energy dispersive X-ray (EDX) measurements of the oxidized surface obtained by oxidizing a commercial surface (CMP-treated surface) at 7 V for 1 min. Figures 8(d) and (e) show SEM images and EDX measurements of the oxidized surface obtained by oxidizing a commercial surface (CMP-treated surface) at 7 V for 10 min, removing the oxide film with hydrofluoric acid, and oxidizing again at 7 V for 1 min. As shown in Figures 8(a) and (b), the oxidation of the CMP surface was not uniform due to the occurrence of large oxide protrusions, and the distribution of oxygen on the oxidized surface was not uniform, concentrating in the regions of oxide protrusions and lines corresponding to SSDs. In contrast, as shown in Figures 8(d) and (e), the oxidation of the surface was relatively uniform, the oxygen on the surface was uniformly distributed, and no preferential oxidation occurred even in scratched regions. This result indicates that the surface was uniformly oxidized after removing the surface damage. These results indicate that the anodic oxidation of SiC occurs preferentially from defects.

[0061] <Comparison of internal stresses of various treated surfaces> Figure 9 shows the Raman spectroscopy measurements of the sliced ​​surface (Slicing), diamond-polished surface (Lapping), and ECMP-treated surface (ECMP). The wavelength of the laser used in the Raman spectroscopy was 532 nm. The change in the nominal focal position (NFP) of the laser during the observation was 8 μm. However, taking into account the refractive index of SiC, the change in the actual focal position (AFP), which represents the actual observation depth of the SiC surface, was estimated to be about 2.7 times that in the case of NFP. The residual stress on the SiC surface was measured by the FTO(2 / 4)E2 (776 cm) of SiC. -1 ) peak shift, and the tensile and compressive stresses are -1 Based on the Raman shift from -510 MPa / cm -1 was calculated using the ratio of

[0062] Figure 9 shows the residual stress in the depth direction observed by confocal Raman microscopy on various processed surfaces. As shown in Figure 9(a), many irregular cracks and granular SiC were observed on the sliced ​​surface. The two-dimensional distribution image of residual stress shows that tensile and compressive stresses existed on the sliced ​​surface, with the maximum value exceeding 200 MPa, and the tensile stress on the test line reached a maximum depth of about 16.2 μm from the surface. As shown in Figure 9(b), many scratches and pits were observed on the surface processed by conventional lapping with a polishing pressure of 19.6 kPa using a #4000 diamond lapping plate (average grain size range of 2–4 μm) due to the mechanical removal of SiC. The residual stress on the diamond-lapped surface was concentrated at the position of scratches and pits, and the residual stress and the maximum depth at which it existed (about 3.8 μm) were obviously smaller than those on the sliced ​​surface. In contrast, as shown in Figure 9(c), the residual stress on the diamond-lapped surface was significantly higher than that on the sliced ​​surface at a polishing pressure of 10 mA / cm 2 After 2 hours of ECMP at a current density of 10000, only the anodized layer was removed by the soft ceria grinding wheel, resulting in a scratch-free surface. The inset residual stress image shows the absence of SSD on and below the surface, indicating that a damage-free surface was obtained. Therefore, the ECMP treated surface is more preferable as a final surface finishing step.

[0063] <Introduction of SSD using hard fixed abrasive grains> It was confirmed that scratches and subsurface damages (SSDs) on the SiC surface were preferentially oxidized and had a higher anodization rate than the undamaged areas in the anodization process. Therefore, it is expected that the material removal rate (MRR) of slurry-less ECMP can be further improved by introducing shallow SSDs on the SiC surface during ECMP. As shown in Figure 9, residual stress layers with thicknesses of about 20 μm and 4 μm have been observed on the sliced ​​SiC wafer surface and the diamond-lapped surface, respectively.

[0064] The MRR of slurry-less ECMP can be further improved by inducing shallow SSD on the SiC surface during ECMP. The ECMP process is divided into two stages: ECMP with hard abrasives and ECMP with soft abrasives. The SSD layer on the slice surface is very thick, so the MRR needs to be improved, and therefore hard abrasives are used. The shallow SSD induced by hard abrasives during ECMP can promote the anodization and increase the oxidation rate, thus greatly increasing the MRR. After the deep SSD is removed, only a shallow SSD layer remains on the SiC surface, which can be removed by ECMP with soft abrasives for a short time.

[0065] <Polishing Experiment of the Present Invention> In order to confirm the SSD caused by different polishing bodies (grinding wheels), mechanical polishing (MP) of CMP-treated 4H-SiC (0001) surface was performed to compare and evaluate the SSD caused by ceria polishing body50 and the SSD caused by other polishing bodies. Therefore, the polishing bodies used were vitrified-bonded ceria with an average grain size of 1 μm (range 0.5-2 μm, #8000), an alumina grinding wheel with an average grain size of 1 μm (0.5-2 μm, #8000), and a diamond grinding wheel with an average grain size of 0.2 μm (0-0.5 μm, #20000), and the SiC surface was polished. The MP parameters were spindle rotation speed: 1500 rpm, polishing pressure: 140 kPa, feed rate X: 10 mm / s, feed rate Y: 10 mm / s, reciprocating distance X: 8 mm, reciprocating distance Y: 8 mm, polishing time: 30 min, flow rate: 380 mL / min, and electrolyte: 1 wt% NaCl aqueous solution.

[0066] In the MP experiment, a cross-polishing motion was used and the SiC surface was polished for 30 min. Figure 10 shows the scanning white light interferometer (SWLI) images of the SiC surface mechanically polished with different abrasive grains. Although many large scratches were observed on the surface polished with the ceria grindstone, the scratches were very shallow and had a relatively small surface roughness without microcracks on the surface, as shown in Figure 10(a). The surface polished with the alumina grindstone had many large scratches after MP similar to the ceria grindstone, as shown in Figure 10(b), but many microcracks were observed, indicating brittle fracture of the SiC surface. Since the grain size of the abrasive grains is very small (less than 2 μm), the large scratches on the surface polished with the ceria and alumina grindstones are likely due to the agglomeration of the abrasive grains. These results indicate that a single small ceria and alumina abrasive grain can hardly remove the SiC surface, and it is difficult to form a uniform SSD layer by applying the ceria and alumina grindstones.

[0067] Figure 10(c) shows the surface polished with the #20000 diamond wheel. No obvious scratches were observed, and the surface roughness was much smaller than that obtained by the ceria wheel. These results suggest that almost no SSD was induced on the SiC surface. On the surface obtained by MP with the #8000 diamond wheel, a pitted surface was observed, but no scratches were observed. Although the surface is rough compared with other surfaces, it is much smaller than that of the sliced ​​SiC surface. Moreover, the defects are very uniform on the surface polished with the #8000 diamond wheel, which is favorable for ECMP to obtain a smooth surface. Figure 11 shows the cross-sectional views of the polished surfaces polished with different wheels using MP. The SiC surface was almost removed by the ceria, alumina, and #20000 diamond wheels. In the MP with the #8000 diamond wheel, a polishing depth of about 10.4 μm was observed, but since the polishing time was 30 min, the MRR can be calculated to be 20.8 μm / h. Therefore, it was confirmed that the #8000 diamond grinding wheel is very promising for removing deep SSD on the SiC surface and improving the MRR of ECMP.

[0068] Next, the 4H-SiC surface was polished by slurry-less ECMP using different polishing bodies (grinding wheels). To investigate the promotion performance of slurry-less ECMP in MRR, ECMP was performed on the CMP-treated surface of SiC using ceria, alumina, #20000 diamond, and #8000 diamond grinding wheels. The polishing conditions were current density: 10 mA / cm 2 , spindle speed: 1500 rpm, polishing pressure: 140 kPa, feed rate X: 10 mm / s, feed rate Y: 10 mm / s, reciprocating distance X: 8 mm, reciprocating distance Y: 8 mm, polishing time: 30 min, electrolyte: 1 wt% NaCl aqueous solution, flow rate: 380 mL / min. A cross-polishing motion was used in ECMP to polish the CMP-treated surface for 30 min.

[0069] Figure 12 shows SWLI images of SiC surfaces treated by ECMP using different abrasive bodies (grinding wheels). As shown in Figure 12, little SiC surface was removed by ceria, alumina, and #20000 diamond wheels in MP, so these results suggest that the increase in MRR was caused by the anodization of SiC surface enhanced by SSD induced during ECMP. The SSD layer induced by #8000 diamond wheel was much thicker than that induced by alumina, therefore, a much higher MRR was obtained by #8000 diamond wheel. Moreover, in the case of #8000 diamond wheel, the MRR in ECMP increased by more than two times that of MP, which suggested that the softening of SiC surface by anodization was also very effective in improving the MRR of ECMP with diamond wheel.

[0070] Figure 13 shows the polishing depth of the polished surface processed using different polishing bodies (grinding wheels). After anodization, the SiC surface was removed by all four grinding wheels. The polishing depth obtained by applying the #20000 diamond grinding wheel, the ceria grinding wheel, and the alumina grinding wheel was 1.8 μm, 2 μm, and 4.2 μm, respectively. However, they were much smaller than the polishing depth of about 22.3 μm and MRR of about 44.6 μm / h obtained by the #8000 diamond grinding wheel.

[0071] As shown in Figure 12(a), in the case of the ceria grinding wheel, a smooth surface with Sq surface roughness of 0.624 nm and Sz surface roughness of 5.457 nm was obtained. Meanwhile, in the case of the alumina grinding wheel in Figure 12(b), a surface with large pits and wide scratches was obtained by ECMP, similar to the surface obtained by MP of the CMP-processed surface using the alumina grinding wheel in Figure 10(b). Since the introduction of SSD into the SiC surface by the alumina grinding wheel was not uniform, the sites of SSD were preferentially oxidized, which caused a rough surface, with the Sq surface roughness reaching 24.757 nm and the Sz surface roughness reaching 191.360 nm. These roughness values ​​are not favorable for the subsequent final polishing of the SiC surface. As shown in Figure 12(c) and (d), the topography of the surface treated by ECMP using the #20000 diamond grinding wheel was similar to that obtained with the #8000 diamond grinding wheel, but the surface roughness was lower. It is believed that the oxide layer was not completely removed with the #20000 diamond grinding wheel because the polishing depth was the shallowest. As shown in Fig. 12(d), the surface treated by ECMP using the #8000 diamond grinding wheel was almost the same as the surface obtained by MP shown in Fig. 10(d), and ECMP performed mechanical removal of the SiC surface.

[0072] Next, the polishing results of MP and ECMP using different polishing bodies (grindstones) are shown in Figures 14 to 17. Figure 14 shows the results for the #8000 ceria grindstone, Figure 15 shows the results for the #8000 alumina grindstone, Figure 16 shows the results for the #20000 diamond grindstone, and Figure 17 shows the results for the #8000 diamond grindstone. In each figure, (a) on the left shows the polished surface of MP, (b) in the center shows the polished surface of ECMP, and the figure on the right shows the polishing depth. As a result, when the #8000 ceria grindstone was used, the results obtained were Sa = 1.098 nm, Sq = 1.385 nm, Sz = 9.226 nm for MP, and Sa = 0.480 nm, Sq = 0.624 nm, Sz = 5.457 nm for ECMP (Figure 14). When using the #8000 alumina grindstone, the results were Sa=2.487nm, Sq=3.154nm, Sz=24.908nm for MP, and Sa=18.832nm, Sq=24.757nm, Sz=191.360nm for ECMP (Figure 15). When using the #20000 diamond grindstone, the results were Sa=0.611nm, Sq=0.747nm, Sz=4.802nm for MP, and Sa=3.708nm, Sq=4.643nm, Sz=31.842nm for ECMP (Figure 16). When a #8000 diamond grinding wheel was used, the results obtained were Sa = 7.515 nm, Sq = 9.471 nm, Sz = 70.816 nm for MP, and Sa = 6.912 nm, Sq = 8.691 nm, Sz = 68.262 nm for ECMP (Figure 17).

[0073] From these results, when the #8000 ceria grinding wheel is used, the surface roughness is excellent, but the MRR is small at about 4 μm / h. In contrast, when the #8000 diamond grinding wheel is used, the surface roughness is not so good, but the MRR is very high at about 44.5 μm / h. Furthermore, when the #20000 diamond abrasive grains are used, the MRR is as low as when the ceria grinding wheel is used. Therefore, it was found that the #8000 diamond grinding wheel is suitable for high-speed polishing processes. It was also confirmed that the #8000 ceria grinding wheel is suitable for finish polishing.

[0074] Since it is expected that the MRR of slurry-less ECMP can be significantly improved by using a hard fixed abrasive, a #8000 diamond grinding wheel was selected to carry out a high-speed polishing process in the initial polishing stage of the sliced ​​SiC surface (manufactured by TankeBlue Semiconductor Co. Ltd.) to improve the MRR of ECMP. The polishing conditions were: current density: 10 mA / cm 2 , spindle speed: 1500 rpm, polishing pressure: 140 kPa, feed speed X: 10 mm / s, feed speed Y: 10 mm / s, reciprocating distance X: 8 mm, reciprocating distance Y: 8 mm, polishing time: 20 min, electrolyte: 1 wt% NaCl aqueous solution, flow rate: 380 mL / min. The grinding wheels are #8000 diamond grinding wheels and #8000 ceria grinding wheels.

[0075] The sliced ​​SiC surface was first polished by ECMP with a #8000 diamond wheel for 20 minutes to quickly remove the deep SSD, and then the resulting surface was polished by ECMP with a ceria wheel for 30 minutes to remove the shallow SSD. The left side of Figure 18 shows a SWLI image of the sliced ​​SiC surface, which was very rough with a Sq surface roughness of 0.110 μm and a Sz surface roughness of 1.081 μm. As shown in the center of Figure 18, after only 20 minutes of ECMP using a #8000 diamond wheel, the Sq surface roughness was reduced to 9.768 nm and the Sz surface roughness was reduced to 79.910 nm. This result indicates that the deep SSD on the sliced ​​surface was removed. As shown on the right side of FIG. 18, after only 30 minutes of additional ECMP with the ceria wheel, the Sq surface roughness was reduced to 0.429 nm, and the Sz surface roughness was reduced to 3.299 nm, which is comparable to the surface after direct ECMP with the ceria wheel for 2 hours. These results indicate that the planarization and smoothing of the sliced ​​surface was achieved by the ECMP process of the present invention. The resulting SiC surface can be further smoothed by performing a finish polish. FIG. 19 shows the cross-sectional view of the polished area at different ECMP stages. After 20 minutes of ECMP with the #8000 diamond wheel, a polishing depth of about 21 μm was obtained, and after 30 minutes of additional ECMP with the ceria wheel, the polishing depth increased to about 25.6 μm. MRRs of 63 μm / h and 9.2 μm / h were obtained for ECMP with the diamond and ceria wheels, respectively. These results showed that the roughness of the sliced ​​wafers was reduced from 0.11 μmSq to less than 0.5 nmSq within 50 minutes.

[0076] <Rough polishing process and finish polishing process in low-speed polishing process> Next, we consider how to improve the surface roughness by optimizing the anodization parameters. Although a SiC surface with sub-nanoscale surface roughness was obtained, there is still a lot of high-frequency surface roughness on the polished surface. We confirmed that the anodization of the SiC surface becomes uniform with increasing oxidation current density, but many small pits still occur on the oxidized surface. In order to obtain an atomically smooth surface, oxide protrusions should not occur during anodization. On the other hand, LSV measurements showed that a potential of 2.4 to 3.5 V resulted in passivation of the SiC surface, and no oxide protrusions were generated at this potential. Therefore, it is considered that additional ECMP with a certain potential in the passivation state can be utilized in finishing the surface obtained by ECMP with a high current density.

[0077] Therefore, the ECMP with high current density is considered as rough ECMP, where the rapid removal of SSD and the significant reduction of surface roughness were performed to obtain the overall planarization of the SiC surface. Then, the ECMP with lower potential is used as the finishing ECMP, which can remove the micron-sized high-frequency surface roughness of the surface generated by the rough ECMP and further reduce the surface roughness. To verify the feasibility of this sequential ECMP process, the rough ECMP and the finishing ECMP were performed on sliced ​​4H-SiC (0001) surfaces. The polishing conditions of the rough polishing step using #8000 ceria abrasive grains were: current density: 10 mA / cm 2 The polishing conditions for the final polishing process are: potential: 3V, spindle rotation speed: 1500rpm, polishing pressure: 140kPa, feed speed: 10mm / s, reciprocating distance: 8mm, polishing time: 120min, electrolyte: 1wt% NaCl aqueous solution, flow rate: 380mL / min.

[0078] First, the SiC surface was exposed to 10 mA / cm 2The rough polishing was performed by ECMP at a current density of 0.428 nm for 2 h, and then a finish ECMP was performed on the rough polished surface at a potential of 3 V for 1 h. The left image in Fig. 20 is a SWLI image of the as-sliced ​​SiC surface. And the center image in Fig. 20 shows a SWLI image of the SiC surface obtained by rough ECMP, and the right image in Fig. 20 shows a SWLI image of the SiC surface after polishing by finish ECMP. It is clear that the high frequency features on the surface obtained by rough ECMP were removed by the finish ECMP, and an atomically smooth surface with Sq surface roughness of 0.428 nm and Sz surface roughness of 3.481 nm was obtained.

[0079] FIG. 21(a) shows an AFM image of the surface obtained by rough ECMP, and FIG. 21(b) shows an AFM image of the surface obtained by finish ECMP. By the low-speed polishing process, i.e., the rough polishing process and the finish polishing process, the micron-sized high-frequency features on the SiC surface were completely removed, and a surface with a step-terrace structure was obtained. These results show that the slurry-less ECMP of the present invention is very effective in manufacturing SiC wafers in both the rough polishing process and the fine polishing process. The slurry-less ECMP of the present invention can replace grinding, lapping, and CMP, simplifying the manufacturing process of SiC wafers. EXAMPLES

[0080] FIG. 22 is a simplified diagram of an ultrasonic assisted electrochemical mechanical polishing (UAECMP) device in which ultrasonic vibration is added to the above-mentioned slurry-less ECMP. The SiC wafer 41 is placed under an opening 43 opened on the bottom surface of a container 42 in a sealed state via a rubber ring 44, and is held on the upper surface of a metal plate 45. A spindle 47 with a grindstone 46 attached to its lower end is placed vertically against the polished surface of the SiC wafer 41, and the grindstone 46 is pressed with a predetermined pressure. An electrolyte 48 is poured into the spindle 42, and the polished surface of the SiC wafer 41, an electrode 49 at the lower end of the spindle 47, and the grindstone 46 are immersed in the electrolyte 48. A positive potential is applied from a power source 50 to the SiC wafer 41 via a metal plate 45, and a negative potential is applied to the electrode 49 via the spindle 47, and the voltage and current density are adjusted to a predetermined value to cause anodization. Furthermore, the spindle 47 is rotated to polish and remove oxides with the grindstone 46. Furthermore, an ultrasonic generator 51 is installed on the bottom surface of the metal plate 45, and ultrasonic vibration is applied to the polished surface of the SiC wafer 41 via the metal plate 45.

[0081] As shown in Fig. 23, the tips of the abrasive grains 52 of the grindstone 46 are pressed against the polished surface of the SiC wafer 41. The abrasive grains 52 are hard, specifically diamond, which is harder than SiC. When the SiC wafer 41 is subjected to ultrasonic vibration in this state, the abrasive grains 52 locally impact the polished surface. As a result, many shallow SSDs are introduced into the polished surface of the SiC wafer 41. This ultrasonic introduction process is performed during polishing, so the positions of the abrasive grains 52 constantly change, and SSDs are formed uniformly on the polished surface.

[0082] It was also found that ultrasonic vibration increases the anodization rate even on the surface of the SiC wafer 41 that is not in contact with the abrasive grains 52. FIG. 24 shows the results of examining the depth of the anodization with and without ultrasonic vibration. The oxidation conditions were voltage: 20 V, oxidation time: 20 minutes, electrolyte: 1 wt% NaCl aqueous solution, EC: 1.8 S / m, ultrasonic frequency: 40 kHz, and ultrasonic output: 100 W. The oxide film partially formed on the surface of the SiC wafer 41 was removed by etching with HF, and the depth of the recesses formed by this was measured. As a result, the average oxidation depth increased by about two times with ultrasonic waves compared to without ultrasonic waves.

[0083] In addition, as shown in Figure 25, the surface roughness of the SiC wafer after removing the oxide film was improved from Sq: 2.76 nm without ultrasonic waves to Sq: 1.68 nm with ultrasonic waves. This shows that applying ultrasonic waves is also effective in improving surface roughness. The processing time was adjusted so that the anodization depth without ultrasonic waves and with ultrasonic waves were almost the same.

[0084] Next, a SiC wafer was actually polished by ECMP while applying ultrasonic vibration. The polishing conditions were: voltage: 20V, polishing pressure: 70kPa, shaft rotation speed: 1500rpm, polishing time: 60min, feed rate: 10mm / s, ultrasonic frequency: 40kHz, ultrasonic output: 100W. The electrolyte was 1wt% NaCl aqueous solution, EC: 1.897S / m, and the grindstone was a vitrified bonded ceria grindstone (#8000, grain size: 1μm). The cross section of the polished surface is shown in Figure 26, and the material removal rate increased by more than three times by applying ultrasonic waves. However, the surface roughness was worse than that of normal ECMP, but this was due to the influence of the residual oxide film, and this could be resolved by increasing the polishing pressure to increase the polishing rate and making the polishing rate higher than the oxidation rate.

[0085] Next, the oxide film removal characteristics were evaluated using quartz glass. The polishing conditions were: polishing pressure: 70 kPa, shaft rotation speed: 1500 rpm, polishing time: 30 minutes, feed speed: 10 mm / s, electrolyte: 1 wt% NaCl aqueous solution, EC: 1.897 S / m, ultrasonic frequency: 42 kHz, ultrasonic output: 100 W. The grinding wheel used was a vitrified bonded ceria grinding wheel (#8000, grain size: 1 μm). The results of the oxidation depth are shown in Figure 27. This shows that the application of ultrasonic waves increases the polishing depth of quartz glass by 1.4 times.

[0086] Figure 28 shows the results of polishing the aforementioned SiC wafer using UAECMP under the aforementioned polishing conditions, but with the polishing pressure doubled to 140 kPa, increasing the polishing rate. Figure 28(a) shows an image of the surface state, and Figure 28(b) shows the results of XPS measurement. The surface roughness was excellent, at Sq: 0.322 nm, better than the Sq: 0.696 nm obtained for a surface polished by ECMP without ultrasonic waves. It was also found that no oxide film remained on the polished surface.

[0087] Figure 29 shows the results of slurry-less UAECMP. The AFM image on the left side of Figure 29 shows that small pits are present on the surface polished by UAECMP, but a damage-free surface was obtained. The surface roughness was Sa: 0.920 nm, Sq: 1.188 nm, and Sz: 9.534 nm. The diamond lapping surface and the UAECMP polished surface were observed with a confocal Raman microscope at a wavenumber resolution of 0.1 cm. -1 , shift range ±0.5cm -1 As a result of measuring the residual stress in the depth direction observed in the figure, it was found that residual stress was observed on the diamond-lapped surface in the center (SSD: ~4 μm), but no residual stress was observed on the UAE CMP polished surface on the right (SSD: 0 μm), indicating that the surface was of high quality. EXAMPLES

[0088] FIG. 30 shows a polishing apparatus of the fourth embodiment, which is an image of practical use. This apparatus is composed of a high-speed polishing apparatus A using a hard fixed abrasive polishing body and a low-speed polishing apparatus B using a soft fixed abrasive polishing body. The high-speed polishing apparatus A and the low-speed polishing apparatus B have a common structure except for the polishing body, so the structure will be explained using the high-speed polishing apparatus A. As shown in FIG. 30(a), the high-speed polishing apparatus A has a cylindrical container 62 on a rotating table 61, a metal plate 64 is placed on the bottom surface of the container 62 via an insulator 63, and a hard fixed abrasive polishing body 65 is attached to the upper surface of the metal plate 64. An electrode rod 66 extends upward from the center of the metal plate 64. At the radius of the hard fixed abrasive polishing body 65, a SiC wafer 67 is held by a rotatable wafer holder 68 via a metal electrode plate 69. An electrode rod 70 extends upward from the center of the metal electrode plate 69. An electrolyte 71 is stored in the container 62. The SiC wafer 67 is used as a working electrode (WE), the metal plate 64 is used as a counter electrode (CE), and an electrode 72 immersed in an electrolyte 71 is used as a reference electrode (RE), all of which are connected to a potentiostat 73. The rotating electrode rods 66 and 70 are connected to the potentiostat 73 via slip rings.

[0089] The low-speed polishing apparatus B shown in Fig. 30(b) has a structure in which a soft fixed abrasive grain polishing body 74 is attached instead of the hard fixed abrasive grain polishing body 65 of the high-speed polishing apparatus A. Since the other structures are similar to those of the high-speed polishing apparatus A, the same components are given the same reference numerals and their explanations are omitted. After removing deep SSD from a SiC wafer 67 in the high-speed polishing apparatus A, the SiC wafer 67 is transferred to the low-speed polishing apparatus B for finish polishing. It is also possible to use one polishing apparatus and replace the hard fixed abrasive grain polishing body 65 with the soft fixed abrasive grain polishing body 74. EXAMPLES

[0090] FIG. 31 shows a polishing apparatus of the fifth embodiment, which is an image of practical use. This polishing apparatus C has a structure that combines the functions of the high-speed polishing apparatus A and the low-speed polishing apparatus B. The structure of the polishing apparatus C is substantially the same as that of the high-speed polishing apparatus A except for the polishing body, so the same components are given the same reference numerals and their description is omitted. In the polishing body 75 of this embodiment, a plurality of hard fixed abrasive grain polishing bodies 76 and soft fixed abrasive grain polishing bodies 77 are arranged in a nested manner, and a mode in which the hard fixed abrasive grain polishing body 76 protrudes upward and a mode in which the soft fixed abrasive grain polishing body 77 protrudes upward can be selected by a lifting mechanism (not shown). That is, FIG. 31(a) shows a high-speed polishing mode in which the hard fixed abrasive grain polishing body 76 protrudes upward, and FIG. 31(b) shows a low-speed polishing mode in which the soft fixed abrasive grain polishing body 77 protrudes upward. In this case, there is no need to change the SiC wafer 67 from high-speed polishing to finish polishing at low-speed polishing, improving work efficiency.

[0091] Previous experiments have shown that applying ultrasonic vibration increases the oxidation rate of SiC (see Figure 24), the polishing rate of quartz glass (oxide film) (see Figure 27), and the MRR of SiC (see Figure 26). However, in previous experiments, the electrolyte was used at room temperature and the temperature was not controlled. Therefore, we investigated the temperature change of the electrolyte with respect to the polishing time in ECMP and UAECMP when the electrolyte temperature was not controlled. The sample was 4H-SiC (0001), N type, on-axis, diamond lapping surface. The polishing conditions were as follows: electrolyte: 1wt% NaCl aqueous solution, EC: 1.8S / m, grinding wheel: vitrified bonded ceria grinding wheel (♯8000, grain size: 1μm), voltage: 25V, polishing pressure: 70kPa, shaft rotation speed: 1500rpm, polishing time: 60min, feed rate: 10mm / s. In the case of UAECMP, the ultrasonic frequency was 42 kHz and the ultrasonic power was 100 W. As a result, it was found that the temperature of the electrolyte increased with the polishing time in ECMP and UAECMP, as shown in Figure 32. As expected, the increase in the electrolyte temperature was more noticeable in UAECMP.

[0092] Here, it is known that the anodization rate increases due to ultrasonic vibration even on the surface of a SiC wafer that is not in direct contact with the abrasive grains, so it can be assumed that the temperature of the electrolyte has some effect on the MRR. Therefore, we first investigated how the oxidation rate changes with the temperature of the electrolyte. First, we investigated the relationship between temperature and oxidation depth using an experimental device that can control the temperature of the electrolyte. The sample was a diamond-lapping surface of 4H-SiC (0001), N type, on-axis. The oxidation depth was measured by etching the oxide film formed on the sample with HF. The anodization conditions were voltage: 25 V, oxidation time: 20 min, electrolyte: 1 wt% NaCl aqueous solution, EC: 1.8 S / m, and temperature: 25, 30, 40, 50, and 60°C. The relationship between the temperature of the electrolyte and the oxidation depth is shown in Figure 33. It was found that the oxidation rate increases exponentially with an increase in the temperature of the electrolyte.

[0093] In addition, the relationship between the current density and the oxidation depth at different temperatures was investigated using two types of samples. The samples were 4H-SiC (0001), N type, CMP surface with 4° off and diamond lapping surface. The anodization conditions were current density: 0.1 to 25 mA / cm. 2 , oxidation time: 20 min, electrolyte: 1 wt% NaCl aqueous solution, EC: 1.8 S / m, temperature: 25, 40, 60°C. The relationship between current density and oxidation depth is shown in Figure 34. As the current density increases, the oxidation rate of SiC saturates, so the polishing rate (same as MRR) cannot be increased, but it was found that the saturation value of this oxidation rate increases with an increase in the temperature of the electrolyte, and the polishing rate increases significantly. It was also confirmed that the maximum oxidation rate of the damaged diamond lapping surface was higher than that of the undamaged CMP surface, and that the difference became smaller as the temperature increased.

[0094] Next, to investigate the nature of the phenomenon in which the MRR increases with ultrasonic application, mechanical polishing (MP) and ultrasonic mechanical polishing (UAMP) were performed without applying voltage using the device shown in Figure 22. The sample was 4H-SiC (0001), N type, on-axis, CMP surface. The common polishing conditions were: electrolyte: 1 wt% NaCl aqueous solution, EC: 1.8 S / m, grinding wheel: vitrified bond ceria grinding wheel (♯8000, grain size: 1 μm), polishing pressure: 70 kPa, shaft rotation speed: 1500 rpm, feed rate: 10 mm / s. For UAMP, the ultrasonic frequency was 42 kHz and the ultrasonic output was 30 W. The polishing time for MP was 30 minutes, and the polishing time for UAMP was 30 minutes and 1 minute.

[0095] The MP-polished surface and two types of UAMP-polished surfaces with different polishing times were observed using a confocal Raman microscope with a wavenumber resolution of 0.1 cm. -1 , shift range ±0.1cm -1 Figure 35 shows the results of measuring the residual stress in the depth direction observed with ultrasonic vibration. No residual stress was observed on the MP polished surface on the left side of Figure 35, while residual stress was observed on the UAMP polished surfaces to which ultrasonic vibration was applied in the center and right side. The UAMP polished surface with a polishing time of 30 minutes in the center of Figure 35 had slightly more residual stress, but a similar level of residual stress was introduced to the UAMP polished surface with a polishing time of 1 minute on the right side. It is noteworthy that even with ceria abrasive grains, which are softer than SiC, shallow SSDs are introduced to the SiC wafer surface by applying ultrasonic vibration. It was found that the increase in MRR due to the application of ultrasonic vibration is largely due to the introduction of shallow SSDs.

[0096] Therefore, in order to confirm the effect of increasing the material removal rate (MRR) by applying ultrasonic vibration, the MRR of ECMP and UAECMP was compared by controlling the temperature of the electrolyte. The sample was 4H-SiC (0001), N type, on-axis, CMP surface. The common polishing conditions were: voltage: 25 V, polishing time: 60 min, electrolyte: 1 wt% NaCl aqueous solution, EC: 1.8 S / m, temperature: 25, 30, 50, 60 °C, grinding wheel: vitrified bonded ceria grinding wheel (♯8000, grain size: 1 μm), polishing pressure: 70 kPa, shaft rotation speed: 1500 rpm, feed rate: 10 mm / s. In the case of UAECMP, the ultrasonic frequency was 42 kHz, and the ultrasonic output was 30 W. The results are shown in Figure 36. It was found that the material removal rate of UAECMP was about four times that of ECMP at the same electrolyte temperature. The effect of increasing the MRR by applying ultrasonic waves is clear. It is also clear that the increase in electrolyte temperature contributes to the increase in MRR, regardless of whether ultrasound is applied or not.

[0097] As shown in Figures 33 and 36, the polishing rate can be significantly improved by increasing the temperature of the electrolyte in all polishing stages of ECMP and UAECMP. Also, the polishing rate can be more accurately controlled by controlling the temperature of the electrolyte. EXAMPLES

[0098] FIG. 37 shows a local polishing apparatus with a temperature control function according to the sixth embodiment of the present invention. This embodiment is a structure in which a temperature control function is added to the local polishing apparatus shown in FIG. 4, and the same components are given the same reference numerals and their description is omitted. The local polishing apparatus with a temperature control function according to this embodiment includes a recovery pump 79 that recovers the electrolyte 27 from the container 26 and sends it to a thermostatic bath 78, a supply pump 80 that sucks up the electrolyte 27 controlled to a predetermined temperature from the thermostatic bath 78 and supplies it to the rotary joint 32 of the spindle 24 equipped with a grinding wheel 25 at its tip, and a circulation piping system 81 that connects them, and also includes a thermometer 82 that measures the temperature of the electrolyte 27 in the container 26. The thermostatic bath 78 is configured by immersing a storage container 84 with good thermal conductivity in a water bath in a heat-insulating container 83 equipped with a heat exchange function, and the electrolyte 27 is sent to the storage container 84 and maintained at a predetermined temperature. The temperature control function may have any structure. For example, a part of the continuous circulation piping system 81 may be a heat pipe that passes through a heat exchanger and circulates the electrolyte at a predetermined temperature using a single circulation pump. EXAMPLES

[0099] 38 and 39 show an ultrasonically assisted electrochemical mechanical polishing (UAECMP) apparatus according to the seventh embodiment of the present invention. This embodiment is a polishing apparatus suitable for planarizing and polishing a planar workpiece, for example, a SiC wafer 101. In this polishing apparatus, a container 104 is fixed on a rotatable disk 102 via an insulator 103, a metal plate 105 serving as a cathode is laid on the bottom surface, and a plurality of ultrasonic transducers 106, ... are arranged in a vertically penetrating state. A grindstone 107 is attached to the upper end of each ultrasonic transducer 106, and the container 104 is filled with an electrolyte 108 so that the grindstone 107 is immersed. The SiC wafer 101 is held by a rotatable wafer holder 109 and pressed against the grindstone 107 with a predetermined load in the electrolyte 108. The wafer holder 109 is adsorbed to a vacuum chuck 112 provided on the lower surface of a rotary head 110 via an insulating layer 111. The SiC wafer 101 connected to a potentiostat 113 is applied with a positive potential as a working electrode (WE), the metal plate 105 is used as a counter electrode (CE), and a reference electrode (RE) is placed in the electrolyte 108. Reference numeral 114 in the figure denotes a personal computer for control, and 115 denotes an ultrasonic generator for supplying power to the ultrasonic transducer 106. Of course, it is preferable to add a temperature control function for the electrolyte to this polishing apparatus. FIG. 40 shows an example of a modification of the UAECMP apparatus of the seventh embodiment to a more practical form, in which the number of the ultrasonic transducers 106 is increased to apply ultrasonic vibration uniformly to the front surface of the SiC wafer 101 for polishing. EXAMPLES

[0100] FIG. 41 shows a local UAECMP device according to the eighth embodiment of the present invention, which is suitable for polishing curved surfaces by numerical control. A workpiece 201 such as SiC is held by a holder (not shown), and a polishing head 202 is arranged facing the polishing surface of the workpiece 201. An electrolyte is leaked from the polishing head 202, and the relative position is changed while being pressed with a predetermined load to polish any curved surface. The polishing head 202 is attached to an ultrasonic vibration unit 203 fixed to a spindle (not shown), and a grinding wheel 204 with a hemispherical tip is formed. As shown in FIG. 41(b), the grinding wheel 204 has a structure in which abrasive grains 206 are embedded in a wet body 205 through which an electrolyte can permeate, and the electrolyte supplied from the spindle through the ultrasonic vibration unit 203 leaks from the wet body 205 and is supplied to the polishing surface. Then, a voltage is applied from a power source 207 to the workpiece 201 as the positive electrode and to a metal (not shown) placed in the electrolyte in the polishing head 202 as the negative electrode. Of course, the ultrasonic vibration unit 203 is supplied with power from an ultrasonic generator (not shown) to apply ultrasonic vibration to the polishing head 202. Here, porous glass, highly water-absorbent resin, or the like is used as the wet body 205. In order to control the temperature of the electrolyte, it is also preferable to add a temperature control function to the electrolyte supply system or to incorporate a heater in the polishing head 202. EXAMPLES

[0101] FIG. 42 shows a local UAECMP apparatus according to the ninth embodiment of the present invention, which is also suitable for polishing curved surfaces by numerical control. This polishing apparatus has a structure similar to that of the polishing apparatus of the eighth embodiment, and is provided with a supply channel 208 and a recovery channel 209 in the polishing head 202, rather than an electrolyte from a wet body 205. The polishing head 202 of this embodiment is attached to an ultrasonic vibration unit 203 fixed to a spindle (not shown), and is a grinding wheel 204 with a hemispherical tip. The head 202 is provided with a cylindrical portion 210 on the outer periphery of the grinding wheel 204, and the space between the cylindrical portion 210 and the grinding wheel 204 serves as the supply channel 208, and a through hole provided in the center of the grinding wheel 204 serves as the recovery channel 209. The electrolyte is recovered by a circulation pump 211 provided in the recovery piping system of the recovery flow path 209, and sent to a thermostatic bath 212 equipped with a temperature control function. The electrolyte maintained at an appropriate temperature is sent to the supply flow path 208 while adjusting the flow rate with a flow meter 213 and a valve 214 provided in the supply piping system. In this case, the electrolyte is present only on a limited surface of the polishing surface of the workpiece 201, and the formation of an oxide film 215 is also localized. The other configurations are the same as those of the eighth embodiment. The relationship between the supply flow path 208 and the recovery flow path 209 may be reversed. [Industrial Applicability]

[0102] The present invention can be used for surface finishing of single crystal SiC wafers and single crystal GaN wafers. It can also be used for shape creation and surface finishing of CVD-SiC and cemented carbide (WC) molds. It can also be used for manufacturing lightweight SiC mirrors for space telescopes. [Explanation of symbols]

[0103] 1 SiC wafer, 2 spindle, 3 insulating layer; 4 wafer holder; 5 grindstone, 6 opening, 7 metal plate; 8 insulating layer; 9 Rotary table, 10 Electrolyte, 11 potentiostat, 12 vessel, 13 oxide layer, 21 SiC wafer, 22 XY table, 23 copper plates, 24 spindles, 25 grindstone, 26 container, 27 Electrolyte, 28 Potentiostat, 29 Electrode, 30 Slip ring, 31 supply pipe; 32 rotary joint; 33 Circulation pump, 41 SiC wafer, 42 container, 43 opening, 44 rubber ring, 45 metal plate, 46 grinding wheel, 47 spindle, 48 electrolyte, 49 electrodes, 50 power supplies, 51 ultrasonic generator, 52 abrasive grain, 61 Rotary table, 62 Container, 63 Insulator, 64 Metal plate, 65 Hard fixed abrasive polishing body, 66 Electrode rod, 67 SiC wafer, 68 wafer holder, 69 metal electrode plate, 70 electrode rod, 71 electrolyte, 72 electrode, 73 Potentiostat, 74 Soft fixed abrasive polishing body, 75 Abrasive body, 76 Hard fixed abrasive abrasive body, 77 Soft fixed abrasive polishing body, 78 Thermostatic chamber, 79 Recovery pump, 80 Supply pump, 81 Circulation piping system, 82 Thermometer, 83 Insulated container, 84 Storage container, 101 SiC wafer, 102 disk, 103 Insulator, 104 Container, 105 metal plate, 106 ultrasonic transducer, 107 grinding wheel, 108 electrolyte, 109 wafer holder, 110 rotating head, 111 insulating layer, 112 vacuum chuck, 113 Potentiostat, 114 Personal computer, 115 Ultrasonic generator, 201 Workpiece, 202 Polishing head, 203 ultrasonic vibration unit, 204 grinding wheel, 205 Wet body, 206 Abrasive grain, 207 power source; 208 supply channel; 209 recovery flow passage, 210 cylindrical portion, 211 Circulation pump, 212 Thermostatic bath, 213 Flowmeter, 214 Valve, 215 Oxide film, A high-speed polishing equipment, B low speed polishing equipment, C Polishing equipment.

Claims

1. In the presence of an electrolyte, an anodizing process in which a voltage is applied to a workpiece as an anode to oxidize the surface of the workpiece; a polishing process in which oxides formed on the surface of the workpiece are polished and removed using a fixed abrasive polishing body having abrasive grains of a predetermined hardness and grain size fixed to a substrate; and (c) simultaneously or alternately proceeding with a polishing rate in the polishing process higher than an oxidation rate in the anodizing process, a high-speed polishing process that provides a high material removal rate for the workpiece, even removing scratches and deep subsurface damage introduced during manufacture; a low-speed polishing step in which the material removal rate of the workpiece is low and oxides resulting from shallow damage are removed and planarized; and the high-speed polishing step is provided with a damage introducing means for introducing uniformly shallow damage under the surface of the workpiece.

2. 2. The polishing method assisted by anodization according to claim 1, wherein the high speed polishing step uses a hard fixed abrasive polishing body having hard abrasive grains, the hardness of which is higher than that of the workpiece, fixed to a substrate.

3. 3. The polishing method utilizing anodic oxidation according to claim 2, wherein the high-speed polishing step is performed under high current density conditions in which the potential of the workpiece is set to a high potential higher than the passive potential of an oxide.

4. 2. The polishing method using anodization according to claim 1, wherein the low-speed polishing step uses a soft fixed abrasive polishing body having soft abrasive grains fixed to a substrate, the soft abrasive grains having a hardness lower than that of the workpiece and higher than that of the oxide.

5. 5. The polishing method using anodic oxidation according to claim 4, wherein the low-speed polishing step includes a finish polishing step performed under a low current density condition in which the potential of the workpiece is set to a low potential equal to or lower than the passive potential of the oxide.

6. 6. The polishing method using anodic oxidation according to claim 5, wherein the low-speed polishing step includes a rough polishing step performed before the finish polishing step under a high current density condition in which the potential of the workpiece is set to a high potential higher than the passive potential of an oxide.

7. The polishing method using anodization according to any one of claims 1 to 6, wherein the damage introduction means is friction between a hard fixed abrasive polishing body having hard abrasive grains harder than the workpiece fixed to a substrate and the surface of the workpiece.

8. 8. The polishing method assisted by anodization according to claim 1, wherein ultrasonic vibration is applied to the polishing surface from the workpiece side or from the fixed abrasive polishing body side.

9. 9. The polishing method assisted by anodic oxidation according to claim 8, wherein said damage introducing means is ultrasonic vibration applied to said polishing surface.

10. The method for polishing with the aid of anodic oxidation according to any one of claims 1 to 9, further comprising controlling a temperature of the electrolytic solution.

11. The method for polishing assisted by anodization according to any one of claims 1 to 10, wherein the workpiece is single crystal SiC.

12. 8. The method of polishing with the aid of anodization according to claim 2 or 7, wherein the hard fixed abrasive polishing body is a diamond grindstone having an average grain size of 1 μm (range 0.5 to 2 μm, #8000).

13. 5. The method of claim 4, wherein the soft fixed abrasive polishing body is a ceria grinding wheel.

Citation Information

Patent Citations

  • Artificial kidney apparatus

    JP1988029655A

  • Anodic oxidation surface treated base and polishing method therefor

    JP1995052030A

  • Method of manufacturing semiconductor device and method of polishing semiconductor device

    JP2001326204A

  • Chemical mechanical polishing method for substrate

    JP2001332517A

  • Polishing method, polishing system, plating method and plating system

    JP2002093761A